THE EMPOWERMENT OF ZAKAT AS SOCIAL FINANCIAL PERSPECTIVE OF ISLAM - Hamzah Khaeriyah; Sudirman Sudirman (Universitas Islam Negeri Alauddin Makassar, 2019)
The focus of this research is on the empowerment of Islamic Social finance perspectives in finding the optimal empowerment model. Still not optimal management of zakat funds so that the potential in advancing the economy through social finance can not be achieved. The purpose of this research will reveal some important points as an idea in building up empowering social finance of zakat funds. This research approach is a qualitative perspective using the grounded theory method.Based on the results of the study will produce a basic theory about the empowerment of zakat funds contained in 5T ieprecise target, precise amount, appropriate cost, timely and precise influence.